The 49 steps to a bright life - Murray, Phil (Hodder & Stoghton, 1996)
This text explains that there are 49 steps to a happier and more fulfilling life. It uses the titles of popular songs to help illuminate the ideas, encouraging the reader to recognize and concentrate on his or her story, and shows that each person has the potential to succeed in all areas of life.